2019
DOI: 10.1016/j.jaad.2019.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab drug survival in patients with psoriasis: A multicenter, real-world, retrospective study

Abstract: To the Editor: Secukinumab, an interleukin 17A inhibitor approved for the treatment of moderate-tosevere plaque psoriasis, has shown high levels of clinical efficacy and a favorable safety profile in both short-term and long-term clinical trials. However, in some studies in the real-life setting, secukinumab showed a 73%-78% drug survival at 12 months, shorter than that of other biologic agents, even among biologic-naive patients, and loss of effectiveness was the most common reason for discontinuation. 1-4 To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
30
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 5 publications
13
30
4
Order By: Relevance
“…Regarding secukinumab, drug survival was reported in 83-368 enrolled patients in observation periods ranging from 12 months to 3 years and 4 months. [8][9][10][11] The 12-and 18-month overall drug survivals of secukinumab were 76-83% and 67-78.8%, respectively, and higher drug survival was shown in bio-na€ ıve patients than in bio-experienced patients with or without statistical significance. [8][9][10] Our data showed similar results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding secukinumab, drug survival was reported in 83-368 enrolled patients in observation periods ranging from 12 months to 3 years and 4 months. [8][9][10][11] The 12-and 18-month overall drug survivals of secukinumab were 76-83% and 67-78.8%, respectively, and higher drug survival was shown in bio-na€ ıve patients than in bio-experienced patients with or without statistical significance. [8][9][10] Our data showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] The 12-and 18-month overall drug survivals of secukinumab were 76-83% and 67-78.8%, respectively, and higher drug survival was shown in bio-na€ ıve patients than in bio-experienced patients with or without statistical significance. [8][9][10] Our data showed similar results. One study with 83 patients who were studied for 12 months showed higher drug survival in bio-experienced patients than in bio-naive patients despite no statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although secukinumab has been shown to be well tolerated and effective in treating patients with plaque psoriasis and PsA in multiple clinical trials (7-9,29-34) with up to 5-year follow up (35), randomized controlled trials are likely to enroll patient populations with more stringent inclusion/exclusion criteria and generally the study design allows a short-term observation compared to the real-world setting. A variety of real-world studies have been recently published: some of them analyzed secukinumab drug survival (36)(37)(38)(39), whereas others assessed its efficacy in psoriasis patient populations with peculiar features, or assessing its effectiveness as improvement of DLQI, BSA, PGA, and PASI scores (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Nevertheless, they reported favorable secukinumab safety and effectiveness in terms of mean reduction of PASI value over time, as patient rates achieving PASI 75, PASI 90, and PASI 100 responses at different timepoints, Investigator's Global Assessments or improvements in quality of life measures (11)(12)(13)(14)(15)(16)(17)(18)(19)22).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, latest analyses of 21 clinical trials showed incidence rates of IBD comparable to untreated patients with psoriasis or psoriatic arthritis (57). Newest real-life data are confirming safety and tolerability of the IL-17 inhibitors also in daily practice, mirroring the evidence from clinical trials (58).…”
Section: Experimental and Clinical Evidence For A Role Of Il-17a In Pmentioning
confidence: 91%